Elementary School Childrens Development Viewed from The Children’s Health Perspective: An Integrative Review - Cuevas, Pearl Ed G (Mimbar Sekolah Dasar, 2018)
This study aimed to ascertain the development of elementary school children in the digital age from their health perspective. This integrative review is aimed at creating a health program for elementary school children in order to guide health workers in creating meaningful, focused, and structured activities that will address their health needs in the digital age. The integrative review as a methodology provides a synthesis of knowledge and the applicability of results of significant studies into practice. Its objective is to present the phases of children’s health in an integrative review so that relevant aspects of the literatures will be taken into account when using this methodological resource. As the influence of digital technology-- and especially the internet—has increased, the debate about its effect on elementary school children’s development has grown louder. We wonder, is the internet a threat to their over-all health and well-being? Digital dependency has shown to have a possible impact on brain development and cognition of elementary school children. In conclusion, the digital technology has already changed the world—and as more and more children go online around the world, it is increasingly changing childhood (UNICEF, 2017).